Answer:
-
, 0
Explanation:
8x⁴ + x = 0
factor out x:
x(8x³ + 1) = 0
The zero product property says that one of the terms needs to be equal to 0:
x = 0
8x³ + 1 = 0
Solve for x in the 2nd equation:
8x³ = -1
x³ = -
![(1)/(8)](https://img.qammunity.org/2020/formulas/mathematics/college/oishxf3znbtm7sgua7hx3bnp2grk4mwmno.png)
x = -
![(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ybjkeso7qr5r7js5h0mv9de35dih0sxfpl.png)
When x is either 0 or -
, the product will be equal to zero.
The roots are 0 and -
![(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ybjkeso7qr5r7js5h0mv9de35dih0sxfpl.png)